Tailoring AlGaN nanoalloys with transition metal dopants for enhanced energy storage: A DFT Study - Fatemeh Mollaamin (Acta Chimica Asiana, 2025)
The notable fragile signal intensity close to the parallel edge of the nanocluster sample might be owing to silicon or germanium binding induced non-spherical distribution of AlGaSiN or AlGaGeN heteroclusters. However, a considerable deviation exists from doping atoms of palladium or platinum as electron acceptors on the surface of AlGaPdN or AlGaPtN heteroclusters. Then, magnetic parameters exhibited the same tendency of shielding for palladium or platinum; however, a considerable deviation exists from doping atoms of palladium or platinum as electron acceptors on the surface of Pd–AlGaN or Pt–AlGaN hetero-clusters. Therefore, it can be considered that palladium or platinum atoms in the functionalized AlGaPdN or AlGaPtN might have more impressive sensitivity for accepting the electrons in the process of hydrogen adsorption. The advantages of platinum or palladium over aluminum gallium nitride include its higher electron and hole mobility, allowing platinum or palladium doping devices to operate at higher frequencies than silicon or germanium doping devices. As a matter of fact, it can be observed that doped heteroclusters of AlGaPdN or AlGaPtN might ameliorate the capability of AlGaN for energy storage.